First report of the genus Neocosmocercella Baker and Vaucher, 1983 (Nematoda: Cosmocercidae) parasitizing amphibians from Argentina - Draghi, Regina (2015)
The cosmocercid, Neocosmocercella paraguayensis was recorded for the first time in Argentina parasitizing the hylid frog Phyllomedusa azurea. Morphometric and morphological data of this nematode species are provided, including the presence of bilobed cephalic lips, vesiculated rosette papillae in males and both uteri directed anteriorly in females. This finding constitutes the first record of this genus in Argentina.